Metabolic Syndrome Among People Living with Human Immunodeficiency Virus (HIV) Receiving Antiretroviral Therapy in Mexico - Tatiana Ordóñez-Rodríguez; Luis Antonio Leyva-Alejandro; José Manuel Reyes-Ruiz; Gustavo Martínez-Mier; Roberto Carlos Cortes-Balán; Oscar Faibre-Álvarez; Judith Quistián-Galván; Wendy Marilú Ramos-Hernández; Víctor Bernal-Dolores (Venereology, 2025)
Background/Objectives: In Mexico, there is very little data on the prevalence of metabolic syndrome in people living with human immunodeficiency virus (HIV) receiving antiretroviral therapy (ART), so, determining the number of people with this condition will help to establish measures to treat it promptly. Methods: A descriptive, observational, prospective, cross-sectional study was conducted in a cohort of people living with HIV who signed the informed consent form and were stratified according to the criteria established by the Adult Treatment Panel III (ATP-III) and the Latin American Diabetes Association (ALAD) for the diagnosis of metabolic syndrome. Results: According to the ATP-III and ALAD criteria, 26.5% and 36.3% of people living with HIV receiving ART were diagnosed with metabolic syndrome, respectively. Metabolic syndrome was more prevalent in men than in women, using both classification criteria (ATP-III: 58 men [67.4%] vs. 28 women [32.6%]; ALAD: 84 men [71.2%] vs. 34 women [28.8%]). The median time since HIV diagnosis of the participants with metabolic syndrome was longer than for the participants without metabolic syndrome, using the ALAD criteria (p = 0.023). The time spent on ART among participants with metabolic syndrome was longer than among those without, using the ATP-III criteria (p = 0.011). The CD4+ T-cell count and HIV-RNA detection showed no significant difference between participants with and without metabolic syndrome (p > 0.05). No statistical significance was found concerning ART and metabolic syndrome; it is noteworthy that for participants with dolutegravir/abacavir/lamivudine (DTG/ABC/3TC), the frequency was similar regardless of the criteria used, and different for those who were taking bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF) or were in other schemes (etravirine, darunavir/ritonavir, raltegravir). Conclusions: Our results suggested that 26.5% and 36.3% of the people living with HIV receiving ART included in this study had metabolic syndrome according to ATP-III and ALAD criteria, respectively. These results are consistent with results reported in the Latin American population. Interestingly, both criteria showed a higher frequency of metabolic syndrome in men living with HIV compared to women.